The Ginkgo biloba Extract Reverses the Renal Effects of Titanium Dioxide Nanoparticles in Adult Male Rats - Carlos Enrique Escárcega-González; Irma Guadalupe Reynoso-Andeola; Fernando Jaramillo-Juárez; Haydée Martínez-Ruvalcaba; Francisco A. Posadas del Rio (Biochemistry Research International)
The Ginkgo biloba extract (GbE) is a commercial product used as a nutraceutic herbal remedy in Europe and US. It contains 27% of the polyphenols isorhamnetin, kaempferol, and quercetin, as antioxidants. We used male adult Wistar rats (200–300 g), divided into four groups: control group (treated with 5.0 mg/kg of sodium chloride, intravenous), titanium dioxide nanoparticles (TiO2-NPs) group (5.0 mg/kg, intravenous), GbE group (10 mg/kg, intraperitoneal), and GbE + TiO2-NPs group (treated 24 h before with 10 mg/kg of GbE, intraperitoneal), followed, 24 h later, by 5.0 mg/kg of TiO2-NPs intravenously. The statistical analysis was performed using Student’s t-test for grouped data with ANOVA posttest. The GbE protected renal cells against the effects of TiO2-NPs because it reversed the increased activity of γ-glutamyltranspeptidase and the enzymatic activity of dipeptidylaminopeptidase IV at all times tested (0–5, 5–24, 24–48, and 48–72 h). Also it reversed the glucosuria, hypernatriuria, and urine osmolarity at three times tested (5–24, 24–48, and 48–72). Thus, we conclude that GbE has a beneficial activity in the cytoplasmic membranes of brush border cells on the renal tubules, against the adverse effects that can be produced by some xenobiotics in this case the TiO2-NPs, in experimental rats.